Mobile learning supporting linguistic landscapes exploration: students and teachers as game creators - Marques, M. M. (2022)
Mobile devices are part of modern societies’ day-to-day life. They have been explored for learning purposes with positive results, both at cognitive and emotional levels, in several subject areas. One of the most valued features in these devices, pointed by literature, is their potential in promoting contextual and situated learning. However, the lack of adequate tools and materials regarding the specific contexts in which teachers are embedded, namely in the exploration of linguistic diversity and plurilingual repertoires for educational purposes, incited the proposal of the LoCALL project. This is an Erasmus + project in Cooperation for innovation and the exchange of good practices, which included as an intellectual output the development of a mobile app that supports game-based approaches to explore cities’ Linguistic Landscapes (LL). The app is fed by a web platform where both students and teachers, from k-12 settings, can create multiple-choice games, prompting the players to go through a path that includes several points interesting from the LL point of view, in a cross-subjects approach. This study presents the process of development of the app, which followed a design-based research, for context. However, the focus is on a project-based approach of game creation involving 20 students from an 8th-grade class and 7 teachers in a Portuguese school, in the scope of informal teacher training. This is a mixed-methods study, where data collection included a teachers group interview and students’ questionnaire. The triangulation of students' and teachers’ perceptions regarding this innovative teaching-learning experience was conducted for an analysis that considers different stakeholders' views. Results from the interview indicate a higher motivation of students for learning when using the LoCALL app and platform for LL exploration, which seems to be more intense in the case of students who usually participate less in traditional lessons. Moreover, teachers also reported that this strategy promotes students’ critical thinking and their capacity of observing their surroundings. Students mainly highlighted that the project supported them in learning more about the spaces, curiosities, and touristic points of their city, whilst they were collecting information and creating the game questions. The developed open technological solution (mobile app and web platform) is relevant not only for the European partners participating in this project but also to anyone who is interested in creating innovative resources to explore the educational value of LL.